Intra‐operative assessment of pulmonary artery pressure by transoesophageal echocardiography1. (10th November 2014) - Soliman, D.; Bolliger, D.; Skarvan, K.; Kaufmann, B. A.; Lurati Buse, G.; Seeberger, M. D.
Summary The clinical value of the estimation of systolic pulmonary artery pressure, based on Doppler assessment of peak tricuspid regurgitant velocity using transoesophageal echocardiography, is unclear. We studied 109 patients to evaluate the feasibility of obtaining adequate Doppler recordings, and compared Doppler estimates with values measured using a pulmonary artery catheter in a subset of 33 patients. Tricuspid regurgitation was evaluated at the mid‐oesophageal level at 0–120° using Doppler echocardiography. A Doppler signal was defined as adequate if there was a ≤ 20° alignment and a full envelope. Doppler estimates of systolic pulmonary artery pressure within 10 mmHg and 15% of the value recorded with the pulmonary artery catheter were considered to be in sufficient agreement. Adequate Doppler signals were obtained in 64/109 (59%) patients before and 54/103 (52%) after surgery. Doppler estimates by transoesophageal echocardiography were within 10 mmHg and 15% of values recorded with the pulmonary artery catheter in 28/33 (75%) patients and 22/31 (55%) patients, respectively. In 7 (21%) patients, the echocardiographic Doppler measurement exceeded the measured systolic pulmonary artery pressure by more than 30%. Our study indicates that estimation of the systolic pulmonary artery pressure using transoesophageal Doppler echocardiography is not a reliable and clinically useful method in anaesthetised patients undergoing mechanical ventilation.